Unfortunate Fertility: An Analysis of the Fertility in Pan’s Labyrinth - Wu, Jiaqi (Journal of Theory and Practice in Humanities and Social Sciences, 2024)
This analysis explores how fertility emerges as a complex and troubling theme, intertwining life, death, and patriarchal oppression in Pan’s Labyrinth (2006), directed by Guillermo del Toro through qualitative analysis of the experiences of Carmen, Captain Vidal, and Ofelia, revealing the dire consequences it imposes. Carmen’s pregnancy debilitates her health and restricts her freedom, ultimately leading to her death during childbirth. Vidal, embodying patriarchal tyranny, views Carmen merely as a vessel for producing a male heir, disregarding her life and agency. His obsession with his lineage and the continuation of patriarchal power exacerbates the suffering caused by fertility. Ofelia, observing her mother’s demise and experiencing her own tragic fate, becomes a witness to the cycle of life and death, further underscored by recurring womb-like imagery throughout the film. The narrative underscores that fertility, while vital for life, is deeply intertwined with pain, sacrifice, and the perpetuation of patriarchal norms. Ultimately, the film portrays fertility not as a life-affirming force, but as a mechanism of control and suffering, leading to the tragic downfall of its characters.